Ductile gas barrier poly(ester–amide)s derived from glycolide. Issue 26 (23rd June 2022) - Jang, Yoon-Jung; Sangroniz, Leire; Hillmyer, Marc A.
Abstract : Sustainable poly(ester–amide)s derived from glycolide have been synthesized and their thermal, mechanical, and gas barrier properties have been studied by systematically changing the number of methylene groups. Abstract : Sustainable gas barrier materials, such as polyglycolide, poly(l -lactide), and poly(ethylene 2, 5-furandicarboxylate) are important alternatives to traditional plastics used for packaging where low gas permeability is beneficial. However, high degrees of crystallinity in these materials can lead to undesirably low material toughness. We report poly(ester–amide)s derived from glycolide and diamines exhibiting both high toughness and desirable gas barrier properties. These sustainable poly(ester–amide)s were synthesized from glycolide-derived diamidodiols and diacids. To understand the structure–property relationships of the poly(ester–amide)s, polymers with different numbers of methylene groups were compared with respect to thermal, mechanical, and gas barrier properties. As the number of methylene groups between ester groups increased in the even-numbered series, the melting temperature decreased and oxygen permeability increased. We also found that these polymers are readily degradable under neutral, acidic, and basic hydrolytic conditions. These high-performance poly(ester–amide)s are promising sustainable alternatives to conventional gas barrier materials.